2015
DOI: 10.1515/jelf-2015-0006
|View full text |Cite
|
Sign up to set email alerts
|

Culture, curriculum design, syllabus and course development in the light of BELF

Abstract: Research into the use of BELF, notably through the analysis of authentic data from business contexts, has shown that BELF communication is intrinsically intercultural, with BELF being used in a wide range of settings and with diverse constellations of interlocutors. Yet, whilst business English teaching materials take a range of approaches to culture, they often fail to address the complexity of intercultural communication or integrate it sufficiently in the overall curriculum. In this paper, findings from BEL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 19 publications
0
9
1
Order By: Relevance
“…Accordingly, they can take actions in their ESP classrooms, design and develop materials to cater for these needs and train BELF aware Business students. In addition to raising teacher and learner awareness, what is also of high importance is developing curriculum in the light of BELF research findings as suggested by Pullin (2015).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, they can take actions in their ESP classrooms, design and develop materials to cater for these needs and train BELF aware Business students. In addition to raising teacher and learner awareness, what is also of high importance is developing curriculum in the light of BELF research findings as suggested by Pullin (2015).…”
Section: Resultsmentioning
confidence: 99%
“…Scholars in all of these fields have discussed the implications of their research for pedagogy and, as such, despite their different orientations, they have been identified as having a similar underlying ideology and placed under the Global Englishes umbrella term. Growing interest in the pedagogical implications of the globalisation of English is evident in the publication of entire books on the topic (Alsagoff et al, ; Galloway, ; Matsuda, , ; McKay, ; McKay & Brown, ; Rose & Galloway, ), sections on TESOL in Global Englishes books (Galloway & Rose, ; Jenkins, ; Y. Kachru & Nelson, ; Kirkpatrick, , ; Seidlhofer, ), articles related to Global Englishes in language teaching journals (Cameron & Galloway, ; Cogo & Pitzl, ; Fang & Ren, ; Galloway & Rose, , ; Jenkins, ; Jenkins, Cogo, & Dewey, ; Rose & Galloway, ; Rose & Montakantiwong, ; Sung, ; Suzuki, ; Syrbe & Rose, ), and articles on TESOL in Global Englishes journals (Berns, ; Galloway & Rose, ; Pullin, ). In recent years we have also witnessed reference to Global Englishes in TESOL practitioner books.…”
Section: Global Englishesmentioning
confidence: 99%
“…Instead of it, the term "practitioner" is more acceptable by some researchers. P Pullin, (2015) summarized ftwo roles for the BE "practitioner". The first role is about BE teaching process, which is revealled from BE teaching contexts to the role as a consultant.…”
Section: -Business English Teacher 71-roles Of the Business English Teachermentioning
confidence: 99%